A new sterically loaded pentadentate N3S2 ligand and its zinc complexes - Heinemann, Frank Wilhelm; et al. (Inorganica Chimica Acta, 2007)
In quest of complexes having [MN3S2] cores in the monomeric form and trans-thiolate donor atoms, the new pentadentate thiolate amine py(t)BuN(2)H(2)S(2-)H(2) [=py(t)BuN(2)H(2)S(2)(2-)=2,6-bis(2-mercapto-3, 5-di-tert-butylphenylaminomethyl)pyridine(2-)] has been synthesized. The template condensation reaction of bis(2-mercapto-3,5-di-tert-butylaniline)zinc (II)[Zn((t)Bu(2)ma)(2)] and pyridine-2,6-dicarbaidehyde in methanol at 40 degrees C leads to the formation of imine zinc complex [Zn(py(t)BuN(2)S(2))] (7), which is very unstable and decomposes to give thiazole 5. However, if the template condensation is followed by in situ reduction with an excess of NaBH4, the stable saturated amine complex [Zn(py(t)BuN(2)H(2)S(2))] (8) is formed. Demetallation of zinc complex 8 under acidic conditions leads to the formation of the desired dithiolate py(t)BuN(2)H(2)S(2)-H-2 ligand (9). (C) 2007 Elsevier B.V. All rights reserved.
Keywords: amine sulfur ligands; nitrogenases; template synthesis; steric ligands